Revisiting the Nutritional and Health-Promoting Properties of Soy Protein-Based Food Formulations for Infants and Adults - Ashaolu, Tolulope Joshua; Lee, Chi Ching; Tarhan, Özgür; Rashidinejad, Ali; Jafari, Seid Mahdi (John Wiley and Sons Inc, 2026)
Soy protein (SP), a high-quality, plant-based protein derived from Glycine max (soybean), has gained global prominence as a nutritional staple and a functional ingredient in diverse dietary applications. It not only contains all essential amino acids (AAs), but also its recognition as a complete protein—containing all essential AAs—and its low saturated fat content make SP a valuable component in vegetarian and vegan diets. Despite its growing popularity, the health effects of the SP remain a subject of scientific and public scrutiny, especially in sensitive populations such as infants and older adults. Soy-based infant formulas are commonly used alternatives to cow's milk-based formulas, yet questions persist regarding their safety and the long-term effects of early isoflavone exposure. In adults, SP is investigated for its impact on muscle maintenance, metabolic health, and aging, though individual responses may vary based on age, sex, and metabolic profile. This review aims to critically examine the current evidence on the nutritional value and functionality of SP in infants and adults. We assess the benefits, limitations, and potential health implications of SP across the lifespan. Current evidence supports the safety of soy formulas in term infants, with no adverse neurodevelopmental or endocrine outcomes. In adults, SP consumption is associated with modest lipid-lowering and bone-protective effects, though study heterogeneity remains. Our objective is to provide a nuanced understanding of SP's role in human nutrition and identify areas requiring further scientific inquiry to support informed dietary guidelines and public health policy.
Keywords: Bioavailability; Functional attributes; Nutrition; Plant proteins; Soybean